Current Practice Patterns in the Management of Bell\'s Palsy Among Physiotherapists of Sargodha, Pakistan - Pakeeza Seemal; Jibran Arshad; Saba Hameed; Sabahat Shafique; Maryum Majeed (Iranian Rehabilitation Journal)
Objectives: We intend to find out current practice patterns in managing Bell’s palsy among the physiotherapists of Sargodha, Pakistan. Methods: A cross-sectional study was conducted from May to August 2022. Data were obtained from 50 physiotherapists working in various clinical settings of Sargodha with more than 2 years of clinical experience. They were selected using convenient sampling. A self-designed questionnaire was used to gather all necessary information regarding the physical therapy practice patterns of Bell’s palsy. The obtained data were analyzed by using SPSS software, version 20. Results: Proprioceptive neuromuscular facilitation (PNF) was the preferred (42%) neurodevelopmental technique used in current practice patterns to manage Bell’s palsy. The most used therapeutic exercises by the physiotherapists were facial expression coordination exercises (66%). Also, 44% of physiotherapists used electrical muscle stimulation as the preferred electrotherapeutic modality in their current practice. Soft tissue release (54%) was the most preferred manual therapy technique in Bell’s palsy patients. The combination of electrical muscle stimulation, facial exercises, and biofeedback was the most used (54%) among physiotherapists. Discussion: Current practice for Bell’s palsy treatment includes PNF techniques, facial expression coordination exercises, soft tissue release, and electrical muscle stimulation by most physiotherapists in Sargodha. The most preferred combination was facial exercises, electrical stimulation, and biofeedback.